Facet‐Selective Deposition of Ultrathin Al2O3 on Copper Nanocrystals for Highly Stable CO2 Electroreduction to Ethylene - Li, Hui; Yu, Peiping; Lei, Renbo; Yang, Feipeng; Wen, Peng; Ma, Xiao; Zeng, Guosong; Guo, Jinghua; Toma, Francesca M.; Qiu, Yejun; Geyer, Scott M.; Wang, Xinwei; et al. (Angewandte Chemie International Edition, 2021)
Catalysts based on Cu nanocrystals (NCs) for electrochemical CO2‐to‐C2+ conversion with high activity have been a subject of considerable interest, but poor stability and low selectivity for a single C2+ product remain obstacles for realizing sustainable carbon‐neutral cycles. Here, we used the facet‐selective atomic layer deposition (FS‐ALD) technique to selectively cover the (111) surface of Cu NCs with ultrathin Al2O3 to increase the exposed facet ratio of (100)/(111), resulting in a faradaic efficiency ratio of C2H4/CH4 for overcoated Cu NCs 22 times higher than that for pure Cu NCs. Peak performance of the overcoated catalyst (Cu NCs/Al2O3‐10C) reaches a C2H4 faradaic efficiency of 60.4 % at a current density of 300 mA cm−2 in 5 M KOH electrolyte, when using a gas diffusion electrode flow cell. Moreover, the Al2O3 overcoating effectively suppresses the dynamic mobility and the aggregation of Cu NCs, which explains the negligible activity loss and selectivity degradations of Cu NCs/Al2O3‐10C shown in stability tests. A facet‐selective atomic layer deposition (FS‐ALD) technique was employed to selectively cover the (111) facets of Cu NCs with ultrathin Al2O3, which significantly increases the faradaic efficiency ratio of C2H4/CH4 in both H‐type and GDE flow cells. This Al2O3 overcoating also effectively suppresses the dynamic mobility and aggregation of Cu NCs during CO2RR.